Вплив занять оздоровчим фітнесом на рівень депресії чоловіків зрілого віку - Волощенко, Юрій; Voloschenko, Yurii (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті вивчено вплив занять оздоровчим фітнесом на рівень депресії в чоловіків зрілого віку, які займаються фітнесом понад шість місяців. Дослідження проводили на базі клубів фітнес-мережі «Sport@spa» протягом 2013–2014 рр. Для виявлення впливу засобів оздоровчого фітнесу на рівень депресії чоловіків зрілого віку розроблено комплексну програму тривалістю не менше ніж 300 хв на тиждень, розраховану на п’ять занять. Педагогічний експеримент проводили протягом 24 тижнів. У якості засобів обрано аеробні навантаження помірної інтенсивності тричі на тиждень тривалістю 40 хв, заняття з йоги – двічі на тиждень по 90 хв. Для аналізу результатів дослідження використовували диференціальну діагностику депресивних станів В. А. Жмурова. Установлено, що в групі чоловіків, які займаються оздоровчим фітнесом, значно більше респондентів, у яких відсутня або незначна депресія (39,3 %, порівняно з 23,3 % у групі чоловіків зрілого віку, котрі ведуть малорухливий спосіб життя). The paper studies the impact of employment on health and fitness levels of depression of men of mature age, engaged in more than 6 months. Research was conducted on the base of clubs of fitness network of «Sport@spa» during 2013– 2014 years. To study the influence of the health and fitness levels of depression on men of mature age, we developed a comprehensive program lasting at least 300 minutes a week, calculated on 5 lessons. Pedagogical experiment was carried out for 24 weeks. As agents were chosen aerobic exercise of moderate intensity three times a week for a 40 minutes, namely – a healthy walking and running using cardiovascular equipment. Trainings were held in the morning before work. Besides the three sessions of aerobic orientation, we have used yoga classes 2 times a week lasting for 90 minutes. Trainings are held in the evening. In yoga, except asanas, breathing practices were used. To analyze the results of the study used the differential diagnosis of depression V. A. Zhmurova. It was found that in a group of men who have health and fitness, significantly more respondents who do not have depression or low (39,3 % compared with 23,3 % in the group of middle-aged men who lead a sedentary lifestyle). The level ofthe minimum and mild depression comparable in both groups. Differences exist in the category of «mild depression» (no respondents in the group of middle-aged men engaged in health and fitness over 6 months and 6,7 % in the group of middle-aged men who lead a sedentary lifestyle). Determined that the differences in the results due to the fact that the respondents group of men of mature age who are engaged in health and fitness (over 6months), lead a healthy lifestyle, namely have sufficient motor activity, adhere to sound sleep and rest, nutrition.
Effect of Training on Health and Fitness Levels of Depression Men of Mature Age
Keywords: засоби оздоровчого фітнесу; чоловіки зрілого віку; рівень депресії; хронічний стрес; means of health and fitness; men of mature age; level of depression; chronic stress